Possible influences of vitamin D levels on sleep quality, depression, anxiety and physiological stress in patients with chronic obstructive pulmonary disease: a case control study - Dias, Carlos José (2022)
This study aimed to evaluate the effect of vitamin D deficiency on sleep quality, depression, anxiety, and physiological stress in patients with chronic obstructive pulmonary disease (COPD). We screened for COPD patients with normal (NorVD) (n=24) and insufficient (InsVD) (n=7) vitamin D levels. The Pittsburgh sleep quality index (PSQI), the Beck anxiety inventory (BAI), the Beck depression inventory (BDI) and the Baevsky’s stress index were used for the sleep and psychometric evaluation. The evaluation of sleep quality by PSQI showed that NorVD individuals had higher duration and quality of sleep when compared with the InsVD group. Additionally, the group InsVD presented higher risk of developing sleep quality (OR=6.20; 95% CI=1.334, 29.013; p=0.009). BDI was higher in the InsVD, and this group had a higher risk of developing moderate and severe depression (OR=3.37; 95% CI=0.895, 12.722; p=0.03). The stress index indicated higher values in the InsVD in relation to the NorVD group (InsVD=24±0.8 vs. NorVD=16±0.9), and the group InsVD showed higher risk of developing high and very high physiological stress (OR=7.70; 95% CI=1.351, 43.878; p=0.01). The stress and sleep quality effects were negatively correlated with vitamin D levels. Insufficient levels of vitamin D negatively affect sleep quality and psychometric variables.